Depressive symptoms and overwork among physicians employed at a university hospital in Japan - Toru Maruyama (Journal of Health and Social Sciences)
Introduction: The excessive workload of Japanese hospital physicians is a serious social problem due to effects on their mental health status, as well as the potential for medical errors and lawsuits. The extent of overwork among resident physicians employed at national university hospitals in Japan is unknown and needs to be investigated. Methods: This study used a questionnaire recommended by the Japanese Ministry of Health for hospital physicians working overtime, administered through an interview carried out by an occupational physician during the health surveillance to evaluate: 1) the severity of chronic fatigue; 2) the burden of work; 3) an overwork score derived from these two measures; and 4) presence of depressive symptoms. After the feasibility of the questionnaire was confirmed, both a cross-sectional and a longitudinal study were performed, while statistics analysis included multiple linear regression analysis and chi-square test set at P < 0.05. Results: Most of the overworked physicians were young medical staffs (48%), whereas postgraduate residents formed a small group (10%). In the cross-sectional study (n = 135; mean age 32.7 years ± 5.6), the histograms of scores for the four factors investigated showed a strong positive skewness, while overtime histograms showed a negative skewness at 4, 3, and 2 months prior to the interview with occupational physician, but positive skewness 1 month prior to the interview. The longitudinal study (n = 26) showed an increase or reduction of overtime respectively having a significant impact on exacerbation or improvement of the overwork score (P = 0.028) and depressive symptoms (P = 0.025). Discussion and Conclusions: A strong positive skewness of the histograms for items related to overwork might indicate fear of stigma of mental illness amongst young physicians. Physicians employed at Japanese national university hospitals should be protected by the institution, and the roles of occupational physician and health surveillance are crucial and should be effectively implemented.